Primary mathematics extending knowledge in practice - Hansen, Alice; Sage eBooks (Exeter : Learning Matters, 2008)
The acquisition of subject knowledge, and how to translate this into effective teaching is a major concern for many on initial teacher training courses. This book extends trainees' knowledge of mathematics in a manner which enables them to use it more actively in planning and implementing lessons.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Mathematics -- Study and teaching (Elementary) -- Great Britain; Electronic books